Juwelen van de grootste hedendaagse kunstenaars. (Kruishoutem : Stichting Veranneman, 1975)
Atila ; Baeyens, M. Th. ; Bogart, Bram ; Dierickx, Karel ; Dodeigne, Eugène ; Gilioli, Emile ; Guébels, Monique ; Hamaguchi, Yozo ; Kovacs, François ; Landuyt, Octave ; Leroy, Eugène ; Lindström, Bengt ; Maeyer, Marcel ; Mara, Pol ; de Montpellier, Geoffroy ; Pavlos (Pavlos Dionyssopoulos) ; Pouget, Marcel ; Raveel, Roger ; Revilla, Carlos ; Roldan, Modesto ; Strebelle, Olivier ; Sudre, Jean-Pierre ; Székessy, Karin ; Tapta ; Tovar, Ivan ; Vasarely, Victor ; Verheyen, Jef ; Vermeersch, José ; Wunderlich, Paul
Nederlands
Juwelen van de grootste hedendaagse kunstenaars, Stichting Veranneman, Kruishoutem, 14.10.1975 - 10.01.1976
boek